Gender socialization and capability deprivation on child urban poverty: experiences of Malaysian Indian women - Nithiya Guna Saigaran,; Premalatha Karupiah,; Parthiban S. Gopal, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Child poverty is a crucial component of the urban poverty issue, especially in developing countries, such as Malaysia. The negative effects of deprivation due to gender socialization and capability expansion during childhood are likely to have more difficulty escaping poverty as adults. This study shows the influence of gender socialization experiences of Indian women living in poverty and the state of development of their capabilities due to the constraints faced in their household during their childhood. Hence, Amartya Sen’s capability approach was applied throughout the study to be able to analyze the gender complexities in poor households in two selected urban areas: Seberang Perai Tengah and Timur Laut in Penang, Malaysia. Data were collected from in-depth interviews with ten urban poor Indian women participants who retrospectively described their experiences growing up in poverty during their childhood era. The finding of this study reveals traditional feminine norms, unequal distribution of resources and differential treatment of boys and girls as three important themes. The themes reaffirm that girls face differentiation based on their gender and unequal access to resources in the household. The implications of these findings of the study ensure us to revisit the child poverty from gender lens with more in-depth and multidimensional perspective.